Advances in biological systems for the treatment of high-strength wastewater. (April 2016) - Hamza, Rania Ahmed; Iorhemen, Oliver Terna; Tay, Joo Hwa
Abstract: The elevated organic content of high-strength wastewater makes aerobic treatment systems uneconomical. High-strength wastewaters are preferably treated anaerobically, thus providing a potential for energy generation while producing low surplus sludge. This paper provides an overview of high rate anaerobic digesters developed during the second half of the last century, focusing on anaerobic filter (AF), anaerobic fluidized-bed reactor (AFBR), and upflow anaerobic sludge blanket (UASB), along with their applications in high-strength wastewater treatment. Despite the unique compact design of these systems that combines the treatment and clarification in one reactor, they fail to provide complete stabilization of high-strength wastewater. Further downstream treatment is usually required to meet effluent regulatory limits. Therefore, advanced hybrid systems such as membrane bioreactors (MBRs), combined and integrated anaerobic–aerobic bioreactors are discussed in this review for their potential as effective treatment alternatives. The factors affecting the performance of these hybrid systems have been highlighted. MBRs provide excellent effluent quality with reduced footprint, but their major drawback is membrane fouling which increases maintenance and operating costs. Combined anaerobic and aerobic systems have been developed to provide a cost effective and efficient treatment for high-strength wastewater. Integrated anaerobic–aerobic systems employing biogranulation can provide a promising high-strength wastewater treatment technology. However, the design and operation of the integrated granular bioreactors are still in the development phase with limited data in continuous flow regime and large-scale operation. Long-term granule stability and long start-up are other obstacles. Further research is needed to overcome these shortcomings.